Healthy Older Observers Show Equivalent Perceptual-Cognitive Training Benefits to Young Adults for Multiple Object Tracking - Legault, Isabelle; Allard, Rémy; Faubert, Jocelyn (Frontiers in Psychology, 2013)
The capacity to process complex dynamic scenes is of critical importance in real life. For instance, travelling through a crowd while avoiding collisions and maintaining orientation and good motor control requires fluent and continuous perceptual-cognitive processing. It is well documented that effects of healthy aging can influence perceptual-cognitive processes (Faubert, 2002) and that the efficiency of such processes can improve with training even for older adults (Richards et al., 2006). Here we assess the capacity of older observers to learn complex dynamic visual scenes by using the 3D-multiple object tracking speed threshold protocol (Faubert & Sidebottom, 2012). Results show that this capacity is significantly affected by healthy aging but that perceptual-cognitive training can significantly reduce age-related effects in older individuals, who show an identical learning function to younger healthy adults. Data support the notion that plasticity in healthy older persons is maintained for processing complex dynamic scenes.